Influence of reliability coefficient according to on estimation of high-level responsibility buildings’ safety - Бакулін, Є.А. (Proceedings of National Aviation University (archive), 2004)
The influence analyses of stability coefficient was countered on estimation of safety of buildings and structures of high level of responsibility concerning of their numerical value, serviceability term.